Does mediator use contribute to the spacing effect for cued recall? Critical tests of the mediator hypothesis. Issue 4 (21st April 2018) - Morehead, Kayla; Dunlosky, John; Rawson, Katherine A.; Bishop, Melissa; Pyc, Mary A.
ABSTRACT: When study is spaced across sessions (versus massed within a single session), final performance is greater after spacing. This spacing effect may have multiple causes, and according to the mediator hypothesis, part of the effect can be explained by the use of mediator-based strategies. This hypothesis proposes that when study is spaced across sessions, rather than massed within a session, more mediators will be generated that are longer lasting and hence more mediators will be available to support criterion recall. In two experiments, participants were randomly assigned to study paired associates using either a spaced or massed schedule. They reported strategy use for each item during study trials and during the final test. Consistent with the mediator hypothesis, participants who had spaced (as compared to massed) practice reported using more mediators on the final test. This use of effective mediators also statistically accounted for some – but not all of – the spacing effect on final performance.